The sex effects on changes in jump performance following an isometric back squat conditioning activity in trained adults - Koźlenia, Dawid; Domaradzki, Jarosław (Frontiers in Physiology, 2023)
There are limited data concerning the disparity between males and females in post-activation performance enhancement (PAPE) based on isometry. Therefore, this study aimed to establish if sex differences exist in the PAPE effect on jump height. The study included 30 males and 15 females aged between 19 and 25, with relative strength in the back squat of at least 110% of body weight and a minimum of three years of resistance training experience. A baseline countermovement jump (CMJ) was performed, and the PAPE protocol, which involved three four-second sets of isometric full-back squats with a 1-minute rest interval, was introduced. Five CMJs were performed over the following nine minutes in two minutes rest intervals. Changes (Δ) towards the baseline and each jump height results were calculated and analyzed in the absolute (cm) and relative (%) approach. The repeated measures ANOVA with sex as between-groups effect and time of the changes as within-group effect were conducted. Results showed statistically significant interaction (sex×time) in absolute changes (Δ cm) (F=2.50, η2=0.05, p=0.0447). Post hoc test showed that during the first three minutes, men and women benefited equally, but in the fifth and seventh minutes, the observed changes were greater in men, thus close to significance (p=0.0797, p=0.0786), and in the last minute, the difference was statistically significant (p=0.0309). Also, a statistically significant interaction effect was observed for relative changes (Δ %) (F=4.22, η2=0.09, p=0.0027). At the beginning (the first and third minutes), changes in females were greater than in males, but the differences were insignificant. However, after five minutes, the decrease in females was observed with statistically significant differences in the last minute compared to males (p=0.0391). Chi-Squared analysis indicated that the time to peak performance was insignificant (χ2=7.45, p=0.1140) in both sexes. The introduced PAPE protocol based on isometry improved jump height in both sexes, with performance enhancement recorded in the third-minute post-activation. However, performance decreased in females over the next six minutes, while it was maintained in the male group. Despite the generally positive short-term effects of the protocol on females, the usefulness of the protocol is limited.